Walt Disney's Snow White and the seven dwarfs Robyn Bryant ; image adaptation Atelier Philippie Harchy - Bryant, Robyn; Atelier Philippe Harchy; Walt Disney Company (Montreal, Quebec Brimar Pub., 1993)
A princess takes refuge from her wicked stepmother in the cottage of seven dwarfs.
Keywords: Fairy tales; Folklore -- Germany